Synthesis of popcorn-shaped gallium-platinum (GaPt3) nanoparticles as highly efficient and stable electrocatalysts for hydrogen evolution reaction - Lim, Suh-Ciuan; Chan, Cheng-Ying; Chen, Kuan-Ting; Tuan, Hsing-Yu (Electrochimica acta, 2019)
The hydrogen evolution reaction (HER) holds great promise for clean energy, where electrocatalysts for HER perform as the cathode reaction of water splitting is the critical reaction process on fuel cell. In spite of the rapid growth of alternative materials, platinum (Pt)-based or platinum alloy materials are still the most efficient catalysts for HER. Here, we report a hot-solvent synthesis for producing pop-corn shaped gallium-platinum (GaPt3) nanoparticles, which exhibits intermetallic behavior with abundant uneven surfaces that guarantee the extensive catalytic active edge sites. The electrochemical catalytic activity of GaPt3-based electrode towards HER was demonstrated for the first time, resulting an outstanding performance of only 27 mV overpotential to achieve the 10 mA/cm2 current density and a Tafel slope of 43.3 mV/dec. (vs. RHE) in acidic media, which is rather superior to that of commercial Pt catalysts and a relatively low overpotential (<80 mV) was obtained even operated at large area (5 cm2). Moreover, cycling tests for 10000-cycle CV sweep (−0.3 to 0.2 V vs. RHE) and durability test for 48 h were applied and the performance remains still, thus giving the confirmation to the long-lasting feature of GaPt3 nanoparticles. The GaPt3 nanoparticles with pop-corn like appearance were prepared via hot-solvent synthesis for the first time, exhibit high-performance catalytic and long-lasting properties as HER electrodes. [Display omitted]